Dispersión de una onda electromagnética plana por una partícula cargada - Fernández Chapou, José Luis; Vargas, Carlos Alejandro (CIENCIA ergo-sum; Vol. 7 Núm. 2 (2000): CIENCIA ergo-sum (julio-octubre 2000), 2015)
--